Sex Differences in Human Olfaction: A Meta-Analysis - Sorokowski, Piotr; Karwowski, Maciej; Misiak, Michał; Marczak, Michalina Konstancja; Dziekan, Martyna; Hummel, Thomas; Sorokowska, Agnieszka (Frontiers in Psychology, 2019)
Abstract Although the view that women's olfactory abilities outperform men's is taken for granted, some studies involving large samples suggested that male and female olfactory abilities are actually similar. To address this discrepancy, we conducted a meta-analysis of existing studies on olfaction, targeting possible sex differences. The analyzed sample comprised n = 8 848 (5 065 women and 3 783 men) for olfactory threshold (as measured with the Sniffin Sticks Test; SST), n = 8 067 (4 496 women and 3 571 men) for discrimination (SST), n = 13 670 (7 501 women and 6 169 men) for identification (SST), and a total sample of n = 7 154 (3 866 women and 3 288 men) for works using University of Pennsylvania Smell Identification Test (UPSIT). We conducted separate meta-analyses for each aspect of olfaction: identification, discrimination and threshold. The results of our meta-analysis indicate that women generally outperform men in olfactory abilities. What is more, they do so in every aspect of olfaction analyzed in the current study. However, the effect sizes were weak and ranged between g = 0.08 and g = 0.30. We discuss our findings in the context of factors that potentially shape sex differences in olfaction. Nevertheless, although our findings seem to confirm the “common knowledge” on female olfactory superiority, it needs to be emphasized that the effect sizes we observed were notably small.